Complex systems and physics education - Andrii O. Bielinskyi; Arnold E. Kiv; Yuliya O. Prikhozha; Mykola A. Slusarenko; Vladimir N. Soloviev (Academy of Cognitive and Natural Sciences, 2022)
Synergetics as a scientific area of research is in demand by society. The context of synergetics makes it possible for scientists of different specializations to interact fruitfully in the language of systematic understanding and search for new solutions. The presented work raises the question of how the theory of self-organization can help in the reformation of the higher education system, why this is relevant, and what can lead to the training of both teachers and students within the framework of an interdisciplinary approach. In the future, we will highlight the most important characteristics of complex systems and the simplest and at the same time conceptually simplest methods for analyzing complexity. As part of the complex systems modeling course, which will first be presented to students of physics and mathematics, and then, possibly, to students of other specialties, we present signals of seismic activity, gravitational waves and magnetic activity, and demonstrate how we can identify critical or crash phenomena in such systems. This kind of analysis can serve as a good basis for the formation of professional skills and universal competencies.